INSTITUTIONAL STRENGTHENING OF READ-SI CORN FARMING GROUP READ-SI - Boekoesoe, Yuriko; Mustafa, Ramlan (Jurnal Pengabdian Masyarakat Teknologi Pertanian, 2022)
Institutional Farmers poktan/Gapoktan provide institutional strengthening to farmers through non-formal education which includes activities in knowledge and skills that take place through the teaching and learning process. and well-being. In increasing the knowledge and skills of the community in utilizing agricultural crops, especially corn into plants that have high economic value. Specific targets to be achieved include increasing people's income through strengthening farmer group institutions by conducting counseling, coaching to farmers, especially the corn farmer group under Readsi's guidance.Assistance to farmers in Bunuo Village, Bulango District is very important, especially in terms of institutional strengthening of corn farmer groups. This Readsi assisted farmer group needs to build public awareness in terms of cooperation between extension officers and farmers and other related institutions.The main targets for institutional strengthening are farmer groups and the general public in Bunuo Village, North Bulango District, Bone Bolango Regency. Where the targets are farmers and a combination of farmer groups who are de facto regulators of the family economy and young people who come from farming families. The method used in this activity is training on Institutional Strengthening of Readsi's Corn Farmer Groups. The identification of the problem is how to strengthen the institutions of Combined corn farmer groups in Bunuo village, North Bulango sub-district.Keywords: Institutional, Farmer Group, Economic Value